The direct cost of disability of community-dwelling older persons in Belgium. Issue 10 (8th October 2021) - Cès, Sophie; Lambert, Anne-Sophie; de Almeida Mello, Johanna; Declercq, Anja; Speybroeck, Niko; Annemans, Lieven; Macq, Jean
Abstract: Current policies aim to promote and develop community-based support of disabled elderly persons, yet knowledge of the cost implications is insufficient. Thus, we aimed to estimate, for three disability profiles and three presence levels of the main informal carer (none, non-cohabitant, cohabitant), the cost of formal and informal support currently provided at home in Belgium. In this cross-sectional study, a sample of 5, 642 disabled elderly persons living at home was established between 2010 and 2016. The administrative database of the Belgian public healthcare insurance was merged with other prospective data on social care service utilisation, informal care and disability. The total cost of formal support ranged from €725 to €1, 344 (on average, per person, per month), depending on the three disability profiles identified. Twenty-five per cent of persons with the highest level of disability (important functional limitations and cognitive impairment) and helped by a cohabitant carer, had a low total cost of formal support: below €382 per month. Informal care represented the main cost component of total support costs in the three disability profiles (between 64 and 76%). To prevent the worsening of situations of disabled older persons and their informal carers, better detection of seriously disabled persons with low levels of formal support is crucial.